2018
DOI: 10.5380/bceppa.v35i2.60307
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF THE ADDITION OF SUGARS ON THE THERMOSTABILITY OF BETANIN FROM Beta vulgaris L.

Abstract: O impacto da adição de açúcares na estabilidade das betaninas de Beta vulgaris L. (beterraba) durante o tratamento térmico entre 50 e 80°C e pH 5 foi investigado. A degradação das betaninas pura e adicionada de 10% de sacarose e 40% de frutose seguiu modelo de cinética de primeira ordem e conforme aumento da temperatura, houve aumento dos valores da constante de degradação térmica (Kd), redução na meia-vida e nos valores do tempo de redução decimal (D). Termodinamicamente, apresentando valores de variação de e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…state and the state of the reactants, the positive values indicated that anthocyanin degradation is a nonspontaneous reaction and the similar values indicated similar degradation mechanisms under the different conditions for the same temperature, as observed byIzaguirres et al (2018) when analyzing the influence of the addition of sucrose and fructose on the thermal degradation of betanins. The activation entropy(ΔS) represents the change in disorder of molecules in the system and the negative values obtained suggest that Thermostability of the visual color and anthocyanins from Rio-Grande-Cherry (Eugenia involucrata DC)Oliveira, L. M., & Antelo, F. Braz.…”
mentioning
confidence: 52%
“…state and the state of the reactants, the positive values indicated that anthocyanin degradation is a nonspontaneous reaction and the similar values indicated similar degradation mechanisms under the different conditions for the same temperature, as observed byIzaguirres et al (2018) when analyzing the influence of the addition of sucrose and fructose on the thermal degradation of betanins. The activation entropy(ΔS) represents the change in disorder of molecules in the system and the negative values obtained suggest that Thermostability of the visual color and anthocyanins from Rio-Grande-Cherry (Eugenia involucrata DC)Oliveira, L. M., & Antelo, F. Braz.…”
mentioning
confidence: 52%